Derivational Affixes in "The Adventures of Tom Sawyer" Novel - I G B Wahyu Nugraha Putra; Putu Devi Maharani; Ni Putu Yeni Setiari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Abstract This study aimed to identify the derivational affixes in “The Adventures of Tom Sawyer” novel. The data was all the complex word in “The Adventures of Tom Sawyer” novel. This study focused on analyzing the types and the process of derivational affixes that were found in the data source. This study used qualitative descriptive method to analyze the data. The data were analyzed based on the theory proposed by Katamba (1993) to solve the problem which about the types of derivational affixes. Theory that proposed by Fromkin et al (2013) was used to solve the problem about the hierarchical structure of derivational affixes. This study found 858 data that contained derivational affixes. Derivational prefixes were found in 84 data with percentage 10% such as prefix de-, dis-, en-, im-, in-, ir-, mis-, re- and un-. Then, derivational suffixes were found in 774 data with percentage 90% such as suffix –able, -al, -ance, -ant, -ate, -e, -ed, -en, -ence, -er, -ful, -fy, -ic, -ing, -ion, -ish, -ism, -ity, -ive, -ize, -less, -ly, -ment, -ness, -or, -ous, and –y. This study concluded that derivational suffix was the most dominant type of derivational affixes that found in “The Adventures of Tom Sawyer” novel. Keywords: derivational, affixes, types Abstrak Penelitian ini bertujuan untuk mengidentifikasi derivational affixes dalam novel “The Adventures of Tom Sawyer”. Data dalam penelitian ini adalah semua kata-kata kompleks dalam novel “The Adventures of Tom Sawyer”. Penelitian ini berfokus pada analisis jenis dan proses dari derivational affixes yang terdapat pada sumber data. Penelitian ini menggunakan metode deskriptif kualitatif untuk menganalisis data. Data dianalisis berdasarkan teori yang dikemukakan oleh Katamba (1993) untuk menyelesaikan masalah tentang jenis-jenis derivational affixes. Teori yang dikemukakan oleh Fromkin et al (2013) digunakan untuk menyelesaikan permasalahan tentang struktur hierarki dari derivational affixes. Penelitian ini menemukan 858 data yang mengandung derivational affixes. Derivational prefixes ditemukan pada 84 data dengan persentase 10% yaitu prefix de-, dis-, en-, im-, in-, ir-, mis-, re- dan un-. Derivational suffixes ditemukan pada 774 data dengan persentase 90% yaitu suffix –able, -al, -ance, -ant, -ate, -e, -ed, -en, -ence, -er, -ful, -fy, -ic, -ing, -ion, -ish, -ism, -ity, -ive, -ize, -less, -ly, -ment, -ness, -or, -ous, dan –y. Penelitian ini berkesimpulan bahwa derivational suffixes merupakan jenis yang paling dominan ditemukan dalam novel “The Adventures of Tom Sawyer”. Keywords: derivational, affixes, tipe